INFLUENCE ON SERVICE QUALITY, PRODUCT QUALITY, PRODUCT DESIGN, PRICE AND TRUST TO XL AXIATA CUSTOMER LOYALTY ON STUDENTS OF PGRI KARANG SARI BELITANG III OKU TIMUR VOCATIONAL HIGH SCHOOL - Muhammad Nawawi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Motivation by business rivalry condition of the telecommunications industry from time to time are getting tight, so the company must create a new marketing strategy to maintain and gain market share higher. As for the problem with this study is